THE OPERATION OF HEGEMONY IN A DYSTOPIAN SOCIETY IN LAUREN OLIVER'S DELIRIUM - Bangkit Sandy Pratama; Ikwan Setiawan; Hat Pujiati (Publika Budaya, 2017)
AbstractDelirium is a dystopian novel written by Lauren Oliver. In this novel, there is a depiction on how power and ruling position could be achieved by utilizing a process of negotiating beliefs and values rather than conducting a full coercive domination. The government as the dominant class in this novel initiates its attempt to gain power and ruling position from the people in the society through indoctrinating ideology by the apparatuses before finally gains the consensus from the dominated class. This study presents the elaboration on how hegemony works in a dystopian society which is influenced by the theme of physical-moral destruction, the embodiment of fear and the set of ultimate rules. As the theoretical framework to analyze the data in the novel, this study utilizes the theory of hegemony by Antonio Gramsci, the conception of ideology by Louis Althusser and the idea about coercive discipline by Michel Foucault. The purpose of this study is to delineate the stages of hegemony operation in a dystopian society and relates them to the actual hegemony of the United States as the alternate setting of the novel. The result of this study elaborates that hegemony is a process of gaining power in which the role of coercive elements in it is still needed in order to preserve the power and authority achieved by the dominant class after indoctrinating its ideology. This explains how both of the hegemony operation conducted by either the government in the novel or the United States is able to remain long and strong as it influences several important sectors such as economic, military, technology, culture and etc. From this result, it can be concluded that Delirium as a cultural product acts as one of the hegemonic apparatuses for the United States to strengthen its position as the beacon of the world.